The Witness and Victim Protection Agency's Strategy for Protecting Justice Collaborators in the Murder of Law Enforcement Officers (A Case Study of the Murder of Brigadier Joshua Hutabarat) - Kando, Rachmat; Eddy Sam Karauawan, Donny; Jumiran, Jumiran (Dinasti Research, 2024)
This study was undertaken as part of the Witness and Victim Protection Agency's strategy disclosure for protecting Justice Collaborators in cases involving the murder of law enforcement officials. This needs to be addressed, as the situation is urgent owing to the legal vacuum. The goal of this study is to explore the need for new arrangements with Justice Collaborators. The study method utilised is doctrinal legal research with two methodologies. The first is the approach to legislation governing Witness and Victim Protection, namely the Criminal Procedure Code and Law Number 31 of 2014. The second approach is conceptual, which combines theory and facts. The concern with this study is the Witness and Victim Protection Agency's (LPSK) role in the Protection of Justice Collaborators. Second, how does the Witness and Victim Protection Agency (LPSK)'s method for Protecting Justice Collaborators in the murder of law enforcement personnel compare to Brigadier Josua Hutabarat's murder case study? The problem formulation is critical to how this research can proceed, particularly in describing the issues in this study.